The ASTD leadership handbook - Biech, Elaine; American Society for Training and Development (Alexandria, Va. : ASTD Press, 2010)
The ASTD Leadership Handbook is a compilation of insights, ideas, and tools that will enable individuals, teams, and organizations to develop their leadership capabilities. Topic areas covered in the book are leadership competencies, leadership development, attributes of successful leaders, contemporary leadership challenges, and broadening the leadership discussion.
Includes bibliographical references and index.
Keywords: Leadership -- Handbooks, manuals, etc